Assessment of Longitudinal Gradients in Nematode Communities in the Deep Northern Gulf of Mexico and Concordance with Benthic Taxa. (14th June 2012) - Sharma, Jyotsna; Baguley, Jeffrey G.; Montagna, Paul A.; Rowe, Gilbert T.
Abstract : Meiobenthic nematode assemblages were examined at 16 stations along two transects on the eastern and western boundaries of the deep northern Gulf of Mexico (dNGOM) at depths of 212–3000 m. The highest abundance (297 individuals 10 cm −2 ) and number of genera (71) occurred at stations near the Mississippi River delta. Number of genera decreased with increasing depth, and showed differences in community composition between the east and west regions. The dominant family, Comesomatidae, was represented by Sabatieria that was present at most shallow stations but absent at greater water depths. A significant difference in nematode feeding morphology was observed between depth groups but not between the two transects at different longitudes. Patterns of nematode community structure are congruent with harpacticoid copepods. Overall, the higher abundance and diversity of nematodes in the north-central Gulf of Mexico is consistent with findings of other benthic taxa and reflects organic material loading from the Mississippi River driving deep sea communities in the Gulf. The east-west gradient in composition of nematode communities suggests that nematode assemblages have well-defined distribution patterns similar to other meiobenthic taxa in the GOM but they are not aligned in the bathymetric zones observed in macrofauna, megafauna and demersal fishes.